The impact of wellness on neural learning systems. (1st January 2020) - Colino, Francisco L.; Williams, Chad C.; Hassall, Cameron D.; Binsted, Gordon; Krigolson, Olave E.
Highlights: Reward positivity amplitude was positively associated with wellness. Reward positivity was associated with all of the six dimensions of wellness. Wellness impacts neural functioning responsible for human learning. Abstract: Over the past 20 years there has been an increasing push for people to achieve or maintain "wellness" - a state in which one has not only physical but also mental and social well-being. While it may seem obvious that maintaining a state of wellness is beneficial, little research has been done to probe how maintaining a state of wellness impacts our brain. Here, we specifically examined the impact of wellness on a neural system within the medial-frontal cortex responsible for human reinforcement learning. Sixty-two undergraduate students completed the Perceived Wellness Survey after which they completed a computer-based learnable gambling game while electroencephalographic data were recorded. Within the game, participants were presented with a series of choices that either led to financial gains or losses. An analysis of our behavioral data indicated that participants were able to learn the underlying structure of the gambling game given that we observed improvements in performance. Concurrent with this, we observed an electroencephalographic response evoked by the evaluation of gambling outcomes - the reward positivity. Importantly, we found significant relationships between several aspects of wellness and the amplitude of the reward positivity. Given that the reward positivity is thought to reflect the function of a reinforcement learning system within the medial-frontal cortex, our results suggest that wellness impacts neural function – in this instance one of the systems responsible for human learning.